2013
DOI: 10.1007/s11136-013-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Using the EORTC-QLQ-C30 in clinical practice for patient management: identifying scores requiring a clinician’s attention

Abstract: Purpose Patient-reported outcomes (PROs) are used increasingly for individual patient management. Identifying which PRO scores require a clinician’s attention is an ongoing challenge. Previous research used a needs assessment to identify EORTC-QLQ-C30 cut-off scores representing unmet needs. This analysis attempted to replicate the previous findings in a new and larger sample. Methods This analysis used data from 408 Japanese ambulatory breast cancer patients who completed the QLQ-C30 and Supportive Care Nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 25 publications
(32 reference statements)
10
105
2
Order By: Relevance
“…In recent years, many efforts have been made to define certain cut-off values in order to select those patients with unmet needs for further support. Snyder et al evaluated more than 500 oncologic patients and found a QLQ-C30 global health status cut-off value of 70 to have a sensitivity of up to 86% and a negative predictive value of up to 94% (14, 28). The aim of the current study was to evaluate various potential prognostic features on patients QoL after orthotopic urinary diversion, focusing on preoperative, perioperative as well as postoperative features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many efforts have been made to define certain cut-off values in order to select those patients with unmet needs for further support. Snyder et al evaluated more than 500 oncologic patients and found a QLQ-C30 global health status cut-off value of 70 to have a sensitivity of up to 86% and a negative predictive value of up to 94% (14, 28). The aim of the current study was to evaluate various potential prognostic features on patients QoL after orthotopic urinary diversion, focusing on preoperative, perioperative as well as postoperative features.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to evaluate various potential prognostic features on patients QoL after orthotopic urinary diversion, focusing on preoperative, perioperative as well as postoperative features. To allow a better comparison with existing literature, we analysed the postoperative QLQ-C30 global health status as a continuous parameter as well as following Snyder et al (14). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General tools for capturing patient-reported outcomes and disease-specific tools are increasingly being used in other disease states [18][19][20]. These assessments aid in identifying disease burden or treatment effects that are most important or bothersome to the patient in everyday life.…”
Section: Outcome Goals Beyond Survival In Pediatric Heart Failure Andmentioning
confidence: 99%
“…Both the Phase II and Phase III trials used the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Core 30 (QLQ-C30) and the lung cancer module (QLQ-LC13) 14,51. The QLQ-C30 includes five functional domains, eight symptoms, global health, and financial impact 52,53. Patient reported outcomes are based on their responses in accordance with a four-point scale from “not at all” to “very much”.…”
Section: Implications For Enhanced Quality Of Lifementioning
confidence: 99%